The Influence of Work Environment, Discipline and Work Ethic on Employee Performance(Case study: PTJaya Masawan Putra Sejahtera) (International Journal of Scientific Research and Management (IJSRM), 2024)
The aim of the research is to find out whether the work environment, work discipline and work ethic influence the performance of employees at PT Jaya Masawan Putra Sejahtera, Lemabang Head Office, Palembang City. This type of research is quantitative. The population was 200 people with sampling using saturated samples. Data analysis techniques use descriptive statistical tests, instrument quality tests, classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of the research state that the work environment influences the performance of PT JMPS Lemabang Head Office employees, work discipline influences the performance of PT JMPS Lemabang Head Office employees and work ethic influences the performance of PT Jaya Masawan Putra Sejahtera Lemabang Head Office Palembang City employees and together the work environment , work discipline and work ethic influence the performance of PT JMPS Lemabang Head Office employees.